General theory on taking decisions and its application in the medical assistance area. (IV) - Luis Alberto Corona Martínez (Medisur)
The general theory about decision taking makes reference mainly to those concepts related to decision taking for the individual. The present article is aimed at group decision taking and at stating the principal advantages and disadvantages in group decision taking and at analyzing the implications of these aspects in medical decisions.